BINARY IMAGE FORMING DEVICE - HANIWARA TAKUZO (1992)
PURPOSE:To save the memory capacity by compressing plural picture elements adjacent to a binarizing notice picture element data, storing the result and applying variable control to a real print size of the binarized notice picture element data based on the compressed data. CONSTITUTION:A binarized notice 1 picture element data X in a binary signal A and a binarized peripheral picture element data in preceding and succeeding 3 bits on a same line are subject to data compression by a data compression circuit 41 and the result is stored in a storage circuit 42 as a compressed data. Then the compressed data is discriminated by a discrimination circuit 43 and the result of discrimination is outputted to a pulse generating circuit 34, then the circuit 44 applies variable control to a laser beam diameter and an output position in response to the result of discrimination. Through the constitution above, a 1-dot practical print size and print position with respect to the binarized notice 4 data are subject to variable control by having only to provide a small storage area to the storage circuit 42 and a binary picture excellent in the gradation reproducibility is easily acquired and the print speed is quickened.